Grande Otelo/Sebastião Prata : caminhos e desafios da memória - Santos, Tadeu Pereira dos (2009)
This dissertation analysis the memories made of the image of the artist and composer Grande Otelo/Sebastião Prata. Is makes problematic the images of Otelo built in present time, watching over the shape of its constructions and which interests they attend and, at the same time, seeks for the history of this process by standing out the different versions made over the artist along 20th century. It makes emerge through Grande Otelo a variety of times , that reveal the transformation of this society, analyzing the ways of life different characters. Such analytical path has allowed us to realize how Sebastião Prata has lived a modified experience , in which his multiple histories turn out to be publicity vehicles of innumerable memories.